Dynamics of Islamic Education Thought in the Era of Adolescent Modernization: Dinamika Pemikiran Pendidikan Islam di Era Modernisasi Remaja - Mahdany, Diny (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2023)
Society cannot avoid the era of modernization which provides very significant changes in mindset, behavior, and technology. The era of modernization also has an impact on adolescents who are still in an unstable period so that Islamic education is needed as a signpost so that moral damage does not occur. The changing times urge the dynamics in Islamic education thinking in order to adapt and always be acceptable to the layers of society, especially in dealing with adolescents in the era of modernization. This research uses descriptive research, the data used are sourced from books, scientific works, scientific articles, news on social media, and facts in the field related to the dynamics of Islamic education thought in the era of adolescent modernization. Islamic education thought has a use as input in reconstructing a more universal, inclusive, and integral form of education with Islamic nuances in the face of modernization. The education of adolescents in the era of modernization includes developing children's talents and interests, providing opportunities for children to play, arousing children's interest in worship and learning, awakening children's sense of responsibility for Islam, and strengthening relationships between children, parents, and educators.